(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Forensic science has moved from the margins of criminal adjudication to its core, yet India’s forensic ecosystem remains uneven in capacity, quality, and legal integration. This analytical article examines the institutional architecture of Indian forensics Central and State Forensic Science Laboratories (FSLs), specialized national institutions, accreditation regimes, and investigative interfaces and diagnoses structural bottlenecks such as funding asymmetry, skilled-personnel shortages, accreditation gaps, backlog accumulation, and fragile chain-of-custody practices. It maps the legal scaffolding under the Indian Evidence Act, the Code of Criminal Procedure (CrPC), the Information Technology Act, and recent measures like the Criminal Procedure (Identification) Act, 2022, while flagging unresolved privacy and proportionality concerns after the Puttaswamy privacy ruling. Through illustrative case-law on electronic evidence, scientific opinion, and consent in neuroscientific techniques, it evaluates how procedural rules and judicial standards shape the evidentiary value of forensic outputs. The article contrasts India’s trajectory with international benchmarks the U.S. National Academies (2009) and PCAST (2016) critiques, the Daubert reliability gatekeeping approach, the U.K. Forensic Science Regulator’s statutory powers, and ENFSI/ISO 17025 quality norms—to draw actionable lessons. It proposes a reform agenda centred on (i) a “quality-first” expansion model (mandatory accreditation, validated methods, blind proficiency testing), (ii) workforce pipelines via National Forensic Sciences University (NFSU)–State partnerships, (iii) digital-by-design evidence management integrated with ICJS/CCTNS, (iv) evidence-law updates to harmonize Sections 45, 45-A Evidence Act and Section 79A IT Act with Arjun Panditrao and Anvar P.V., and (v) rights-respecting bio-surveillance policies for DNA, biometric, and AI-enabled forensics. The article concludes that India’s path to trustworthy, timely, and rights-compatible forensic science lies not in volume expansion alone but in rigorous standardization, sustained financing, and legal clarity that aligns scientific validity with constitutional values.